Core temperature parameters in elite sailors during the Tokyo 2020 Olympic Test Event - Grushin, A.; Ogurtsova, M.; Lemesheva, Y.; Zotkin, S.; Ilin, D.; Zelenkova, I. (Preprints, 2021)
Abstract: Objective On the eve of the summer Olympic Games in Tokyo research focus has shifted on the core temperature responses of elite athletes competing in the heat. In the absence of the field data of core temperature during Olympic sailing competition aim of the present study was to identify core temperature response during the Tokyo 2020 Olympic Test Event. Methods Four elite athletes from Olympic sailing (177.5±5.2 cm, 71.1±7.4 kg, body mass index 22.5±1.4 kg/m2, 24.8±3.7 yrs, VO2max 50.6±7.2 mL/min/kg)): 2 males and 2 females participated in the study. Core temperature was recorded using e-Celsius ingestible capsules, heart rate using a heart rate monitor. Ambient conditions in direct sunlight were measured using portable meteo station. Results Core temperature was recorded at water environment via an ingestible capsule in 4 sailors during the training (T), and competition (C), respectively. Ambient conditions in direct sunlight were hot and humid: during training temperature were 30.9°C±1.7°C and relative humidity 81.4%±2.8%, corresponding to a wet-bulb globe temperature of 41°C±4°C and during competition temperature was 31.2°C±2.3°C and relative humidity 87.2%±4.4%, corresponding to a wet-bulb globe temperature of 45.2°C±8.9°C. Core temperature increased during training reaching higher peak values (38.6°C±0.4°C) and during competition (38.9°C±0.4°C). The highest temperature recorded was 39.4°C (C). Conclusion The current study provides unique information into the core temperature parameters under heat stress in elite Olympic sailors during training and race event.